Short Term Transport Policy for India an Approach to Transport Policy in the Next Plan a Consultative Document - Planning Commission (Planning Commission, 1977)
This Paper has been prepared with a view to providing broad guidelines for the formulation of Transport Policy for India for the next Plan, i.e., 1978-83. The Paper is in the nature of a critique and has been prepared on the basis of readily available information and data. Hence, there is no claim to originality.
Government of India, Planning Commission, Transport Policy Planning Project
Government of India, Planning Commission, Transport Policy Planning Project